Use of 5-methoxy-Î±-tetralone in synthesis of diterpenes and sesquiterpenes. - Banerjee, Ajoy; Cabrera, Elvia (Ciencia, 1970)
The transformations of 5-methoxy-α-tetralone are described. Studies on the synthesis of diterpenes veadeiroic acid 9, triptolide 15 and sesquiterpene cacalol 21 from 5-methoxy-α-tetr- alone 1 are discussed. Transformation of 5-methoxy-α-tetralone 1 into 8-methoxy-α-tetralone 27 is described. 5-methoxy-α-tetralone was subjected to several organic reactions to obtain diterpenes and sesquiterpene.